Method for preparing colloidal palladium activating solution by using microfluidic method and colloidal palladium activating solution

Preparation of colloidal palladium activation liquid by microfluidic control method solves the problem of difficulty in taking into account both catalytic activity and stability, and achieves excellent catalytic effect of using low-concentration activation liquid and uniformity of copper plating layer, reducing production costs and avoiding precipitation question.

CN119136423APending Publication Date: 2024-12-13NANTONG SIKETE ELECTRONICS CO LTD

Patent Information

Application Number
CN202411588228.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The catalytic activity and stability of existing colloidal palladium activation liquids are difficult to take into account, which leads to the need for high concentrations of palladium to achieve better catalytic effects, but this leads to waste of resources and high costs. At the same time, the low tin salt content during the synthesis process leads to stability. Insufficient sexual intercourse, precipitation problems are prone to occur.

Method used

The colloidal palladium activation solution is prepared by microfluidic control method. By accurately controlling the mixing and reaction of palladium salt solution and tin salt solution, combined with the styrofoam solution added during the synthesis and maturation stage after synthesis, ensuring that the tin salt and colloid are mixed uniformly, and ascorbic acid is added to Promote the dispersion and oxidation prevention of divalent tin to form a stable Sn(OH)2-Ag colloid.

Benefits of technology

The use of activation liquid with lower concentrations is achieved to achieve excellent catalytic effect and copper depositing effect, while improving the uniformity and bonding force of the copper plating layer, reducing production costs, and avoiding the occurrence of precipitation problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119136423A_ABST
    Figure CN119136423A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing a colloidal palladium activating solution by using a microfluidic method and the colloidal palladium activating solution, the method comprises the following steps: S1, preparing a palladium salt solution, a first tin salt solution and a second tin salt solution, the palladium salt solution is a solution containing palladium chloride and concentrated hydrochloric acid, and the first tin salt solution is a solution containing palladium chloride and concentrated hydrochloric acid; the first tin salt solution is an aqueous solution containing stannous chloride and concentrated hydrochloric acid, and the second tin salt solution is an aqueous solution containing stannous chloride, sodium chloride, ascorbic acid and concentrated hydrochloric acid; s2, mixing and reacting the palladium salt solution and 1 / 3-1 / 2 of the first tin salt solution by adopting a microfluidic method, and dispersing the reaction solution into a second tin salt solution to obtain a mixed solution; and S3, mixing the residual first tin salt solution with the mixed solution by adopting a micro-fluidic method to obtain the colloidal palladium activation solution. By introducing the microfluidic technology, the mixing reaction is more accurately controlled, and the catalytic activity of the colloidal palladium activation solution is improved. By supplementing the tin salt solution, the insufficient stability caused by low tin salt content in the synthesis process is made up.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of printed circuit boards, and in particular to a method for preparing colloidal palladium activation solution by using a microfluidic method and the colloidal palladium activation solution. Background Art

[0002] Printed circuit boards are one of the main components of electronic components. Among them, hole metallization is a key step in the circuit board manufacturing process. Since the hole wall after drilling contains a large amount of non-conductive glass fiber and epoxy resin, it is necessary to plate a layer of conductive material on the insulating hole wall to make them reliably connected to each other. At present, chemical copper deposition is usually used for this treatment, and chemical copper deposition requires the use of an activation liquid as a medium for copper deposition. The most common activation liquid is colloidal palladium activation liquid. The commonly used salt-based colloidal palladium is prepared by mixing palladium salts, tin salts and different additives. The colloidal palladium obtained has a larger particle size, which leads to its low catalytic activity. A higher palladium concentration is required to achieve a better catalytic effect, but it is more wasteful and costly.

[0003] At present, generally, by reducing the amount of tin salt added, the method of adding tin salt in steps can effectively reduce the particle size of the final colloidal palladium product and improve the catalytic activity, but the reduction of tin content in colloidal palladium will reduce the stability of the activation solution. This problem can be compensated to a certain extent by adding tin salt solution to the colloidal palladium activation solution after the synthesis is completed, but since stirring and other methods cannot make the solution and colloidal palladium evenly and completely merged, the colloidal palladium prepared by this scheme is prone to precipitation. Therefore, how to solve the problem of balancing the catalytic activity and stability of the activation solution is a difficulty that needs to be solved urgently. Summary of the invention

[0004] The present invention provides a method for preparing a colloidal palladium activation solution by using a microfluidic method, the method comprising the following steps: S1. Prepare a palladium salt solution, a first tin salt solution, and a second tin salt solution, wherein the palladium salt solution is a solution comprising palladium chloride and concentrated hydrochloric acid, the first tin salt solution is an aqueous solution comprising stannous chloride and concentrated hydrochloric acid, and the second tin salt solution is an aqueous solution comprising stannous chloride, sodium chloride, ascorbic acid, and concentrated hydrochloric acid, and the ratio of concentrated hydrochloric acid in the palladium salt solution to concentrated hydrochloric acid in the first tin salt solution to concentrated hydrochloric acid in the second tin salt solution is 100:(10-15):(3-5), and the ratio of stannous chloride in the first tin salt solution to stannous chloride in the second tin salt solution is (95-105):(30-35); S2, mixing and reacting the palladium salt solution and 1 / 3-1 / 2 of the first tin salt solution by a microfluidic method, and then dispersing the reaction solution into the second tin salt solution to obtain a mixed solution; S3. Using a microfluidic method, the remaining first tin salt solution and the mixed solution are mixed to obtain a colloidal palladium activation solution.

[0005] Preferably, preparing the palladium salt solution comprises: dissolving palladium chloride in concentrated hydrochloric acid to obtain the palladium salt solution; preparing the first tin salt solution comprises: dissolving stannous chloride in water, and then adding concentrated hydrochloric acid to obtain the first tin salt solution; preparing the second tin salt solution comprises: dissolving stannous chloride, sodium chloride, and ascorbic acid in water, and then adding concentrated hydrochloric acid to obtain the second tin salt solution.

[0006] Preferably, in step S2, the palladium salt solution and a portion (1 / 3) of the first tin salt solution are uniformly mixed at a flow rate of 2-4 mL / min using a microfluidic method.

[0007] Preferably, in step S2, the reaction time is 20-30 min; after the reaction solution is dispersed in the second tin salt solution, the temperature is raised to 70-85° C. and stirred continuously, and the temperature is kept for 4-6 h to obtain a mixed solution.

[0008] Preferably, in step S3, the remaining first tin salt solution and the mixed solution are mixed at a flow rate of 3-5 mL / min using a microfluidic method.

[0009] Preferably, in step S3, after mixing and collecting, stirring is continued, and the temperature is kept at 70-85° C. for 0.5-1.5 h, and then cooled to room temperature to obtain the colloidal palladium activation solution.

[0010] Preferably, in step S1, the ratio of concentrated hydrochloric acid in the palladium salt solution, concentrated hydrochloric acid in the first tin salt solution and concentrated hydrochloric acid in the second tin salt solution is 100:(10.8-12.3):(3.1-4.6).

[0011] Preferably, palladium chloride 1-2 g / L, stannous chloride 130-140 g / L, concentrated hydrochloric acid 70-80 mL / L, sodium chloride 160-170 g / L, ascorbic acid 2-3 g / L.

[0012] Preferably, the ascorbic acid is ascorbic acid-silver ion complex solution.

[0013] Preferably, the ascorbic acid-silver ion complex solution is prepared by the following method: Add ascorbic acid and sulfuric acid to the silver ore smelting slag, stir evenly, and then let it stand and soak for 2-3 days; the ratio of ascorbic acid to sulfuric acid is 1:1-3; Solid-liquid separation is performed, and the filter cake is washed with ascorbic acid to obtain an ascorbic acid complex liquid.

[0014] Preferably, in the colloidal palladium activation solution, the colloidal palladium particle size is 40-50 nm.

[0015] A colloidal palladium activation solution, characterized in that it is prepared by the above method.

[0016] Beneficial effects of the present invention: The present invention introduces microfluidic technology, so that the mixing and reaction of the palladium salt solution and the tin salt solution can be more accurately controlled, so as to obtain palladium colloid particles with smaller particle size to improve the catalytic activity of the colloidal palladium activation solution, so that an activation solution with lower concentration can be used to achieve excellent catalytic effect and copper deposition effect.

[0017] The present invention supplements tin salt solution in the aging stage after synthesis, thereby compensating for the insufficient stability caused by low tin salt content in the synthesis process without affecting the particle size of palladium colloid particles. The added solution and colloid are completely and evenly mixed through a microfluidic method, thereby avoiding the occurrence of precipitation problems.

[0018] The invention can prevent the divalent tin ions in the activation solution from being oxidized by adding ascorbic acid with antioxidant properties. The addition of ascorbic acid can effectively promote the adsorption of divalent tin in micropores, and can effectively improve the dispersibility of divalent tin, and improve the uniformity of the copper plating layer and the copper plating bonding force.

[0019] The present invention adopts ascorbic acid complexing liquid, and the hydroxyl groups in ascorbic acid form coordination bonds with silver ions to form ascorbic acid-silver ion complexes with strong stability. In addition, during copper deposition, the ascorbic acid-silver ion complexes act together with tin ions to form Sn(OH )2 -Ag colloid, as the copper ion activation center, effectively reduces the production cost, forms a uniform copper plating layer, and effectively improves the flatness and bonding strength of the copper plating layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The present invention provides a schematic flow chart of a method for preparing colloidal palladium activation solution by using a microfluidic method. DETAILED DESCRIPTION

[0021] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings and embodiments. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0022] like Figure 1 As shown, the present invention provides a method for preparing colloidal palladium activation solution using a microfluidic method, the method comprising the following steps: S1. Prepare a palladium salt solution, a first tin salt solution, and a second tin salt solution, wherein the palladium salt solution is a solution comprising palladium chloride and concentrated hydrochloric acid, the first tin salt solution is an aqueous solution comprising stannous chloride and concentrated hydrochloric acid, and the second tin salt solution is an aqueous solution comprising stannous chloride, sodium chloride, ascorbic acid, and concentrated hydrochloric acid, and the ratio of concentrated hydrochloric acid in the palladium salt solution to concentrated hydrochloric acid in the first tin salt solution to concentrated hydrochloric acid in the second tin salt solution is 100:(10-15):(3-5), and the ratio of stannous chloride in the first tin salt solution to stannous chloride in the second tin salt solution is (95-105):(30-35); S2, mixing and reacting the palladium salt solution and 1 / 3-1 / 2 of the first tin salt solution by a microfluidic method, and then dispersing the reaction solution into the second tin salt solution to obtain a mixed solution; S3. Using a microfluidic method, the remaining first tin salt solution and the mixed solution are mixed to obtain a colloidal palladium activation solution.

[0023] The present invention introduces microfluidic technology, so that the mixing and reaction of the palladium salt solution and the tin salt solution can be more accurately controlled, so as to obtain palladium colloid particles with smaller particle size to improve the catalytic activity of the colloidal palladium activation solution, so that an activation solution with lower concentration can be used to achieve excellent catalytic effect and copper deposition effect.

[0024] The present invention supplements tin salt solution in the aging stage after synthesis, thereby compensating for the insufficient stability caused by low tin salt content in the synthesis process without affecting the particle size of palladium colloid particles. The added solution and colloid are completely and evenly mixed through a microfluidic method, thereby avoiding the occurrence of precipitation problems.

[0025] The invention can prevent the divalent tin ions in the activation solution from being oxidized by adding ascorbic acid with antioxidant properties. The addition of ascorbic acid can effectively promote the adsorption of divalent tin in micropores, and can effectively improve the dispersibility of divalent tin, and improve the uniformity of the copper plating layer and the copper plating bonding force.

[0026] Preferably, the ascorbic acid is ascorbic acid ascorbic acid-silver ion complex liquid. The ascorbic acid-silver ion complex liquid is prepared by the following method: adding ascorbic acid and sulfuric acid to silver ore smelting slag and stirring evenly and then standing and soaking for 2-3 days; the ratio of ascorbic acid to sulfuric acid is 1:1-3; performing solid-liquid separation, and washing the filter cake with ascorbic acid to obtain the ascorbic acid complex liquid. Of course, the preparation method of ascorbic acid ascorbic acid-silver ion complex liquid is not limited to this embodiment, and other conventional preparation methods in the art can be used.

[0027] In this embodiment, ascorbic acid complexing liquid is used. The hydroxyl groups in ascorbic acid form coordination bonds with silver ions to form ascorbic acid-silver ion complexes with strong stability. In addition, during copper deposition, the ascorbic acid-silver ion complexes act together with tin ions to form Sn(OH )2-Ag colloid, which acts as the copper ion activation center, effectively reduces the production cost, forms a copper-plated layer with uniform copper plating, and effectively improves the flatness and bonding strength of the copper-plated layer. The colloidal palladium activation solution prepared in this embodiment has a significantly smaller colloidal palladium particle size and significantly greater stability.

[0028] The method for preparing colloidal palladium activation solution using microfluidics provided by the present invention will be further described below in conjunction with examples.

[0029] Example 1

[0030] (1) Take 2 g of palladium chloride and dissolve it in 65 mL of concentrated hydrochloric acid to prepare the palladium salt solution; take 100 g of stannous chloride and dissolve it in 400 mL of deionized water, and add 7.5 mL of concentrated hydrochloric acid to prepare the first tin salt solution; take 35 g of stannous chloride, 165 g of sodium chloride, and 2.5 g of ascorbic acid and dissolve them in 600 mL of deionized water, and add 2.5 mL of concentrated hydrochloric acid to prepare the second tin salt solution, and keep the temperature at 35 °C.

[0031] (2) The palladium salt solution and one-third of the first tin salt solution were uniformly mixed and reacted at flow rates of 2 mL / min and 4 mL / min using a microfluidic method. The reaction time was 24 min. The reaction solution was then uniformly dispersed in the second tin salt solution, the temperature was raised to 80 °C and stirred continuously, and the temperature was kept for 5 h.

[0032] (3) The remaining first tin salt solution and the insulation solution in (2) were uniformly mixed at a flow rate of 4 mL / min by microfluidics, and stirred continuously after collection, and then kept at 80 °C for 1 h. After the end, the activated solution was cooled to room temperature to obtain a uniform texture without precipitation.

[0033] The particle size test results show that the particle size of colloidal palladium is 40-50 nm.

[0034] The activation solution was diluted to 1% and a copper test was performed, and the result showed that the backlight reached level 9.

[0035] Take 20 mL of 1% concentration activation solution in a colorimetric tube, and pass air into the bottom of the solution through a glass tube at a temperature of 25 °C and an air flow rate of 60 L / h. The period from the beginning of air introduction to the time when the colloidal palladium activation solution changes from brown-black to colorless is recorded as the stabilization time, which is 28 h.

[0036] Example 2

[0037] (1) Take 2 g of palladium chloride and dissolve it in 65 mL of concentrated hydrochloric acid to prepare the palladium salt solution; take 100 g of stannous chloride and dissolve it in 400 mL of deionized water, and add 7.5 mL of concentrated hydrochloric acid to prepare the first tin salt solution; take 35 g of stannous chloride, 165 g of sodium chloride, and 2.5 g of ascorbic acid and dissolve them in 600 mL of deionized water, and add 2.5 mL of concentrated hydrochloric acid to prepare the second tin salt solution, and keep the temperature at 35 °C.

[0038] (2) Slowly and evenly add the palladium salt solution to one third of the first tin salt solution, continue stirring, and react for 8-24 minutes. Then add the reaction solution to the second tin salt solution, raise the temperature to 80°C, continue stirring, and keep warm for 5 hours.

[0039] (3) Add the remaining first tin salt solution to the insulated solution in (2), continue stirring, and continue to insulate for 1 hour. After the end, cool to room temperature to obtain an activation solution.

[0040] There is precipitation in the activation solution.

[0041] The particle size test results show that the particle size of colloidal palladium is 50-60 nm.

[0042] The activation solution was diluted to 1% and a copper test was performed, and the result showed that the backlight reached level 8.5.

[0043] Take 20 mL of 1% concentration activation solution in a colorimetric tube, and pass air into the bottom of the solution through a glass tube at a temperature of 25 °C and an air flow rate of 60 L / h. The period from the beginning of air introduction to the time when the colloidal palladium activation solution changes from brown-black to colorless is recorded as the stabilization time, which is 29 h.

[0044] Example 3

[0045] (1) Take 2 g of palladium chloride and dissolve it in 65 mL of concentrated hydrochloric acid to prepare the palladium salt solution; take 100 g of stannous chloride and dissolve it in 400 mL of deionized water, and add 7.5 mL of concentrated hydrochloric acid to prepare the first tin salt solution; take 35 g of stannous chloride, 165 g of sodium chloride, and 2.5 g of ascorbic acid and dissolve them in 600 mL of deionized water, and add 2.5 mL of concentrated hydrochloric acid to prepare the second tin salt solution, and keep the temperature at 35 °C.

[0046] (2) Slowly and evenly add the palladium salt solution to one-third of the first tin salt solution, continue stirring, and react for 8-24 minutes. Then add the reaction solution to the second tin salt solution, raise the temperature to 80°C and continue stirring. Keep warm for 3 hours.

[0047] (3) Add the remaining first tin salt solution to the insulated solution in (2), continue stirring, and continue to insulate for 3 hours. After the end, cool to room temperature to obtain an activation solution.

[0048] The particle size test results show that the particle size of colloidal palladium is 100-110 nm.

[0049] There is precipitation in the activation solution.

[0050] The activation solution was diluted to 1% and a copper test was performed, and the result showed that the backlight reached level 8.5.

[0051] Take 20 mL of 1% concentration activation solution in a colorimetric tube, and pass air into the bottom of the solution through a glass tube at a temperature of 25 °C and an air flow rate of 60 L / h. The period from the beginning of air introduction to the time when the colloidal palladium activation solution changes from brown-black to colorless is recorded as the stabilization time, which is 30 h.

[0052] Example 4

[0053] (1) Take 2 g of palladium chloride and dissolve it in 65 mL of concentrated hydrochloric acid to prepare the palladium salt solution. Take 35 g of stannous chloride and dissolve it in 400 mL of deionized water, and add 7.5 mL of concentrated hydrochloric acid to prepare the first tin salt solution. Take 35 g of stannous chloride, 165 g of sodium chloride, and 2.5 g of ascorbic acid and dissolve them in 600 mL of deionized water, and add 2.5 mL of concentrated hydrochloric acid to prepare the second tin salt solution. Keep the temperature at 35 °C.

[0054] (2) The palladium salt solution is slowly and evenly added to the first tin salt solution, with continuous stirring, and the reaction is carried out for 8-24 min. Then, the reaction solution is added to the second tin salt solution, the temperature is raised to 80 °C, and continuous stirring is carried out, and the temperature is kept for 6 h.

[0055] The activator has a uniform texture and is free of precipitation.

[0056] The particle size test results show that the particle size of colloidal palladium is 50-60 nm.

[0057] The activation solution was diluted to 1% and a copper test was performed, and the result showed that the backlight reached level 9.

[0058] Take 20 mL of 1% concentration activation solution in a colorimetric tube, and pass air into the bottom of the solution through a glass tube at a temperature of 25 °C and an air flow rate of 60 L / h. The period from the beginning of air introduction to the time when the colloidal palladium activation solution changes from brown-black to colorless is recorded as the stabilization time, which is 18 h.

[0059] Example 5

[0060] (1) Take 2 g of palladium chloride and dissolve it in 65 mL of concentrated hydrochloric acid to prepare the palladium salt solution; take 100 g of stannous chloride and dissolve it in 400 mL of deionized water, and add 7.5 mL of concentrated hydrochloric acid to prepare the first tin salt solution; take 35 g of stannous chloride, 165 g of sodium chloride, and 2.5 g of ascorbic acid and dissolve them in 600 mL of deionized water, and add 2.5 mL of concentrated hydrochloric acid to prepare the second tin salt solution, and keep the temperature at 35 °C.

[0061] (2) The palladium salt solution is slowly and evenly added to the first tin salt solution, with continuous stirring, and the reaction is carried out for 8-24 min. Then, the reaction solution is added to the second tin salt solution, the temperature is raised to 80 °C, and continuous stirring is carried out, and the temperature is kept for 6 h.

[0062] The texture of the activator is relatively uniform, with a small amount of large particles.

[0063] The particle size test results show that the particle size of colloidal palladium is 140-150 nm.

[0064] The activation solution was diluted to 1% and a copper test was performed, and the result showed that the backlight reached level 8.5.

[0065] Take 20 mL of 1% concentration activation solution in a colorimetric tube, and pass air into the bottom of the solution through a glass tube at a temperature of 25 °C and an air flow rate of 60 L / h. The period from the beginning of air introduction to the time when the colloidal palladium activation solution changes from brown-black to colorless is recorded as the stabilization time, which is 22 h.

[0066] Example 6

[0067] (1) Dissolve 1 g of palladium chloride in 65 mL of concentrated hydrochloric acid as the palladium salt solution; dissolve 105 g of stannous chloride in 400 mL of deionized water, add 8 mL of concentrated hydrochloric acid as the first tin salt solution; dissolve 30 g of stannous chloride, 170 g of sodium chloride, and 2 g of ascorbic acid in 600 mL of deionized water, add 3 mL of concentrated hydrochloric acid as the second tin salt solution, and keep the temperature at 35 °C.

[0068] (2) The palladium salt solution and one-third of the first tin salt solution were uniformly mixed and reacted at flow rates of 2 mL / min and 4 mL / min using a microfluidic method. The reaction time was 24 min. The reaction solution was then uniformly dispersed in the second tin salt solution, the temperature was raised to 80 °C and stirred continuously, and the temperature was kept for 5 h.

[0069] (3) The remaining first tin salt solution and the insulation solution in (2) were uniformly mixed at a flow rate of 4 mL / min by microfluidics, and stirred continuously after collection, and then kept at 80 °C for 1 h. After the end, the activated solution was cooled to room temperature to obtain a uniform texture without precipitation.

[0070] The particle size test results show that the particle size of colloidal palladium is 50-65 nm.

[0071] The activation solution was diluted to 1% and a copper test was performed, and the result showed that the backlight reached level 9.

[0072] Take 20 mL of 1% concentration activation solution in a colorimetric tube, and pass air into the bottom of the solution through a glass tube at a temperature of 25 ℃ and an air flow rate of 60 L / h. The period from the beginning of air introduction to the time when the colloidal palladium activation solution changes from brown-black to colorless is recorded as the stabilization time, which is 25 hours.

[0073] Example 7

[0074] (1) Dissolve 1 g of palladium chloride in 65 mL of concentrated hydrochloric acid as the palladium salt solution; dissolve 95 g of stannous chloride in 400 mL of deionized water, add 7 mL of concentrated hydrochloric acid as the first tin salt solution; dissolve 35 g of stannous chloride, 160 g of sodium chloride, and 3 g of ascorbic acid in 600 mL of deionized water, add 2 mL of concentrated hydrochloric acid as the second tin salt solution, and keep the temperature at 35 °C.

[0075] (2) The palladium salt solution and one-third of the first tin salt solution were uniformly mixed and reacted at flow rates of 2 mL / min and 4 mL / min using a microfluidic method. The reaction time was 24 min. The reaction solution was then uniformly dispersed in the second tin salt solution, the temperature was raised to 80 °C and stirred continuously, and the temperature was kept for 5 h.

[0076] (3) The remaining first tin salt solution and the insulation solution in (2) were uniformly mixed at a flow rate of 4 mL / min by microfluidics, and stirred continuously after collection, and then kept at 80 °C for 1 h. After the end, the activated solution was cooled to room temperature to obtain a uniform texture without precipitation.

[0077] The particle size test results show that the particle size of colloidal palladium is 40-50 nm.

[0078] The activation solution was diluted to 1% and a copper test was performed, and the result showed that the backlight reached level 8.5.

[0079] Take 20 mL of 1% concentration activation solution in a colorimetric tube, and pass air into the bottom of the solution through a glass tube at a temperature of 25 °C and an air flow rate of 60 L / h. The period from the beginning of air introduction to the time when the colloidal palladium activation solution changes from brown-black to colorless is recorded as the stabilization time, which is 30 h.

[0080] Example 8

[0081] (1) Take 2 g of palladium chloride and dissolve it in 65 mL of concentrated hydrochloric acid to prepare the palladium salt solution; take 100 g of stannous chloride and dissolve it in 400 mL of deionized water, and add 7.5 mL of concentrated hydrochloric acid to prepare the first tin salt solution; take 35 g of stannous chloride, 165 g of sodium chloride, and 2.5 g of ascorbic acid (ascorbic acid-silver ion complex solution) and dissolve it in 600 mL of deionized water, and add 2.5 mL of concentrated hydrochloric acid to prepare the second tin salt solution, and keep the temperature at 35 °C.

[0082] (2) The palladium salt solution and one-third of the first tin salt solution were uniformly mixed and reacted at a flow rate of 4 mL / min using a microfluidic method. The reaction time was 20 min. The reaction solution was then uniformly dispersed in the second tin salt solution, the temperature was raised to 85 °C and stirred continuously, and the temperature was kept for 6 h.

[0083] (3) The remaining first tin salt solution and the insulation solution in (2) were uniformly mixed at a flow rate of 4 mL / min by microfluidics, and stirred continuously after collection, and then kept at 85 °C for 1.5 h. After the end, the activated solution was cooled to room temperature to obtain a uniform texture without precipitation.

[0084] The particle size test results show that the particle size of colloidal palladium is 40-50 nm.

[0085] The activation solution was diluted to 1% and a copper test was performed, and the result showed that the backlight reached level 9.

[0086] Take 20 mL of 1% concentration activation solution in a colorimetric tube, and pass air into the bottom of the solution through a glass tube at a temperature of 25 °C and an air flow rate of 60 L / h. The period from the beginning of air introduction to the time when the colloidal palladium activation solution changes from brown-black to colorless is recorded as the stabilization time, which is 35 h.

[0087] Example 9

[0088] (1) Take 2 g of palladium chloride and dissolve it in 65 mL of concentrated hydrochloric acid as a palladium salt solution; take 100 g of stannous chloride and dissolve it in 400 mL of deionized water, add 7.5 mL of concentrated hydrochloric acid as the first tin salt solution; take 35 g of stannous chloride, 165 g of sodium chloride, and 2.5 g of ascorbic acid ascorbic acid-silver ion complex solution and dissolve it in 600 mL of deionized water, add 2.5 mL of concentrated hydrochloric acid as the second tin salt solution, and keep it at 35 °C. The ascorbic acid ascorbic acid-silver ion complex solution is obtained by the following method: add ascorbic acid and sulfuric acid to silver ore smelting slag, stir evenly, and then stand and soak for 2 days; the ratio of ascorbic acid to sulfuric acid is 1:1; perform solid-liquid separation, and rinse the filter cake with ascorbic acid to obtain ascorbic acid complex solution; (2) The palladium salt solution and one-third of the first tin salt solution were uniformly mixed and reacted at a flow rate of 2 mL / min using a microfluidic method. The reaction time was 30 min. The reaction solution was then uniformly dispersed in the second tin salt solution, the temperature was raised to 85 °C and stirred continuously, and the temperature was kept for 5 h.

[0089] (3) The remaining first tin salt solution and the insulation solution in (2) were uniformly mixed at a flow rate of 3 mL / min by microfluidics, and the mixture was collected and stirred continuously, and the mixture was kept at 85°C for 1.5 h. After the mixture was cooled to room temperature, an activation solution was obtained. The activation solution had a uniform texture and no precipitation.

[0090] The particle size test results show that the particle size of colloidal palladium is 40-50 nm.

[0091] The activation solution was diluted to 1% and a copper test was performed, and the result showed that the backlight reached level 9.

[0092] Take 20 mL of 1% concentration activation solution in a colorimetric tube, and pass air into the bottom of the solution through a glass tube at a temperature of 25 °C and an air flow rate of 60 L / h. The period from the beginning of air introduction to the time when the colloidal palladium activation solution changes from brown-black to colorless is recorded as the stabilization time, which is 38 h.

[0093] Example 10

[0094] (1) Take 2 g of palladium chloride and dissolve it in 65 mL of concentrated hydrochloric acid as a palladium salt solution; take 100 g of stannous chloride and dissolve it in 400 mL of deionized water, add 7.5 mL of concentrated hydrochloric acid as a first tin salt solution; take 35 g of stannous chloride, 165 g of sodium chloride, and 2.5 g of ascorbic acid ascorbic acid-silver ion complex solution and dissolve it in 600 mL of deionized water, add 2.5 mL of concentrated hydrochloric acid as a second tin salt solution, and keep it warm at 35 ° C, wherein the ascorbic acid ascorbic acid-silver ion complex solution is obtained by the following method: add ascorbic acid and sulfuric acid to silver ore smelting slag, stir evenly, and then stand and soak for 3 days; the ratio of ascorbic acid to sulfuric acid is 1:3; perform solid-liquid separation, and rinse the filter cake with ascorbic acid to obtain ascorbic acid complex solution (2) The palladium salt solution and one-third of the first tin salt solution were uniformly mixed and reacted at a flow rate of 2 mL / min using a microfluidic method. The reaction time was 20 min. The reaction solution was then uniformly dispersed in the second tin salt solution, the temperature was raised to 70 °C and stirred continuously for 4 h.

[0095] (3) The remaining first tin salt solution and the insulation solution in (2) were uniformly mixed at a flow rate of 5 mL / min by microfluidics, and stirred continuously after collection, and then kept at 70 °C for 0.5 h. After the mixture was cooled to room temperature, an activation solution was obtained. The activation solution had a uniform texture and no precipitation.

[0096] The particle size test results show that the particle size of colloidal palladium is 40-50 nm.

[0097] The activation solution was diluted to 1% and a copper test was performed, and the result showed that the backlight reached level 9.

[0098] Take 20 mL of 1% concentration activation solution in a colorimetric tube, and pass air into the bottom of the solution through a glass tube at a temperature of 25 °C and an air flow rate of 60 L / h. The time from the beginning of air introduction to the time when the colloidal palladium activation solution changes from brown-black to colorless is recorded as the stabilization time, which is 37 h.

[0099] Comparative Example 1 (1) Add 0.5 g of palladium chloride to 50 g of 80% hydrochloric acid, then add 50 g of distilled water and stir until completely dissolved; (2) Then add 1.5 g of stannous chloride and stir to dissolve to obtain solution A; (3) Take another 75g of sodium chloride and dissolve it in 300g-350g of distilled water, add 3.5g of sodium stannate and 25g of stannous chloride, stir evenly to obtain solution B; (4) Mix solution A and solution B, then add 20 g of urea and 2 g of resorcinol while stirring, and keep the mixture at 60°C for 2 hours to obtain a colloidal palladium activation solution.

[0100] The particle size test results show that the particle size of colloidal palladium is 85-100 nm.

[0101] The activation solution was diluted to 1% and a copper test was performed, and the result showed that the backlight reached level 8.

[0102] Take 20 mL of 1% concentration activation solution in a colorimetric tube, and pass air into the bottom of the solution through a glass tube at a temperature of 25 °C and an air flow rate of 60 L / h. The period from the beginning of air introduction to the time when the colloidal palladium activation solution changes from brown-black to colorless is recorded as the stabilization time, which is 22 h.

[0103] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing colloidal palladium activation solution using microfluidics, It is characterized in that The method comprises the following steps: S1. Prepare a palladium salt solution, a first tin salt solution, and a second tin salt solution, wherein the palladium salt solution is a solution comprising palladium chloride and concentrated hydrochloric acid, the first tin salt solution is an aqueous solution comprising stannous chloride and concentrated hydrochloric acid, and the second tin salt solution is an aqueous solution comprising stannous chloride, sodium chloride, ascorbic acid, and concentrated hydrochloric acid, and the ratio of concentrated hydrochloric acid in the palladium salt solution to concentrated hydrochloric acid in the first tin salt solution to concentrated hydrochloric acid in the second tin salt solution is 100:(10-15):(3-5), and the ratio of stannous chloride in the first tin salt solution to stannous chloride in the second tin salt solution is (95-105):(30-35); S2, mixing and reacting the palladium salt solution and 1 / 3-1 / 2 of the first tin salt solution by a microfluidic method, and then dispersing the reaction solution into the second tin salt solution to obtain a mixed solution; S3. Using a microfluidic method, the remaining first tin salt solution and the mixed solution are mixed to obtain a colloidal palladium activation solution.

2. The method according to claim 1, It is characterized in that The preparation of the palladium salt solution includes: dissolving palladium chloride in concentrated hydrochloric acid to obtain the palladium salt solution; the preparation of the first tin salt solution includes: dissolving stannous chloride in water, and then adding concentrated hydrochloric acid to obtain the first tin salt solution; the preparation of the second tin salt solution includes: dissolving stannous chloride, sodium chloride, and ascorbic acid in water, and then adding concentrated hydrochloric acid to obtain the second tin salt solution.

3. The method according to claim 1, It is characterized in that In step S2, the palladium salt solution and a portion (1 / 3) of the first tin salt solution are uniformly mixed at a flow rate of 2-4 mL / min using a microfluidic method.

4. The method according to claim 3, It is characterized in that In step S2, the reaction time is 20-30 min; after the reaction solution is dispersed in the second tin salt solution, the temperature is raised to 70-85° C. and stirred continuously, and the temperature is kept for 4-6 h to obtain a mixed solution.

5. The method according to claim 1, It is characterized in that In step S3, the remaining first tin salt solution and the mixed solution are mixed at a flow rate of 3-5 mL / min by microfluidics; after the mixture is collected, stirring is continued, and the temperature is kept at 70-85° C. for 0.5-1.5 h, and then cooled to room temperature to obtain the colloidal palladium activation solution.

6. The method according to claim 1, It is characterized in that In step S1, the ratio of the concentrated hydrochloric acid in the palladium salt solution, the concentrated hydrochloric acid in the first tin salt solution, and the concentrated hydrochloric acid in the second tin salt solution is 100:(10.8-12.3):(3.1-4.6).

7. The method according to claim 1, It is characterized in that The colloidal palladium activation solution comprises: 1-2 g / L palladium chloride, 130-140 g / L stannous chloride, 70-80 mL / L concentrated hydrochloric acid, 160-170 g / L sodium chloride, and 2-3 g / L ascorbic acid.

8. The method according to claim 1, It is characterized in that The ascorbic acid is ascorbic acid-silver ion complex liquid.

9. The method according to claim 8, It is characterized in that The ascorbic acid-silver ion complex solution is prepared by the following method: Add ascorbic acid and sulfuric acid to the silver ore smelting slag, stir evenly, and then let it stand and soak for 2-3 days; the ratio of ascorbic acid to sulfuric acid is 1:1-3; Solid-liquid separation is performed, and the filter cake is washed with ascorbic acid to obtain an ascorbic acid complex liquid.

10. A colloidal palladium activation solution, It is characterized in that Prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing colloid palladium activation liquid by using micro-reactor

    CN103132058A

  • Colloid palladium activator and preparation method thereof

    CN113430505A

  • Colloid palladium activating agent and preparation method and chemical copper deposition process thereof

    CN118726960A

  • Colloidal Palladium Activators and Methods Thereof

    US20100323111A1

Cited By

  • Modified ultra-small palladium cluster activating solution for surface treatment and preparation method thereof

    CN122446159A